An exotic fruit with high nutritional value: Kadsura coccinea fruit - Sun, Jian; Jiang, Yueming; Ismail, Amin; Li, Z.; Prasad, K. Nagendra; Duan, Xuewu; Yang, Bao; Xu, L. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This research was to determine nutritional composition, essential and toxic elemental content, and major phenolic acid with antioxidant activity in Kadsura coccinea fruit. The results indicated that Kadsura coccinea fruit exhibited the high contents of total protein, total fat, ash and essential elements such as calcium (Ca), ferrum (Fe) and phosphorus (P). The levels of four common toxic elements, i.e. cadmium (Cd), mercury (Hg), arsenic (As) and lead (Pb), were lower than legal limits. By high-performance liquid chromatography (HPLC) analysis, gallic acid was identified as major phenolic acid in peel and pulp tissues. Its contents were no significant difference in both tissues. In comparison with two commercial antioxidants, the major phenolic acid extracted from Kadsura coccinea exhibited stronger 1,1-diphenyl-2-picrylhydrazyl radical-scavenging activity and reducing power. Kadsura coccinea fruit is a good source of nutrition and natural antioxidant. It is worthwhile to popularize this exotic fruit around the world.